Technology-mediated experience of space while playing digital sports games - Martin, A. L.; Wiemeyer, J. (International Journal of Computer Science in Sport, 2012)
The general aim of the research project presented in this paper is to analyze the different interactions between human, technology and space within existing theoretical frameworks from different disciplines and to apply these approaches to digital sports games. One particular aim is to investigate the impact of playing expertise or a manipulation of game situations, as well as the use of different technical devices on game experience and how game experiences in the `virtual` world transfer to the `real` world. The core assumption is that the interposition of technology brings up specific transformations in the coupling of perception and action that do not exist in real sports situations. The project is based on a generic framework relating theory and empirical results. In the exploratory phase guideline-based qualitative interviews were applied after playing a dance game. Results confirm the feasibility of the theoretical approach. There is, e.g., a correlation between high scores and the feeling of spatial presence. Participants with previous dancing experience felt more involved in the game. Further studies in the experimental phase are planned to reveal more details.